HDAC inhibitors tune miRNAs in extracellular vesicles of dystrophic muscle‐resident mesenchymal cells. (5th August 2020) - Sandonà, Martina; Consalvi, Silvia; Tucciarone, Luca; De Bardi, Marco; Scimeca, Manuel; Angelini, Daniela Francesca; Buffa, Valentina; D'Amico, Adele; Bertini, Enrico Silvio; Cazzaniga, Sara; Bettica, Paolo; Bouché, Marina; et al.
Abstract: We show that extracellular vesicles (EVs) released by mesenchymal cells (i.e., fibro–adipogenic progenitors—FAPs) mediate microRNA (miR) transfer to muscle stem cells (MuSCs) and that exposure of dystrophic FAPs to HDAC inhibitors (HDACis) increases the intra‐EV levels of a subset of miRs, which cooperatively target biological processes of therapeutic interest, including regeneration, fibrosis, and inflammation. Increased levels of miR‐206 in EVs released by FAPs of muscles from Duchenne muscular dystrophy (DMD) patients or mdx mice exposed to HDACi are associated with enhanced regeneration and decreased fibrosis. Consistently, EVs from HDACi‐treated dystrophic FAPs can stimulate MuSC activation and expansion ex vivo, and promote regeneration, while inhibiting fibrosis and inflammation of dystrophic muscles, upon intramuscular transplantation in mdx mice, in vivo . AntagomiR‐mediated blockade of individual miRs reveals a specific requirement of miR‐206 for EV‐induced expansion of MuSCs and regeneration of dystrophic muscle s, and indicates that cooperative activity of HDACi‐induced miRs accounts for the net biological effect of these EVs. These data point to pharmacological modulation of EV content as novel strategy for therapeutic interventions in muscular dystrophies. Synopsis: Pharmacological modulation of microRNA content in extracellular vesicles released by FAPs of Duchenne Muscular Dystrophy (DMD) muscles exposed to epigenetic drugs (HDAC inhibitors) has therapeutic effects via combinatorial targeting of events implicated in DMD pathogenesis. HDAC inhibitors (HDACis) modulate miRNA content of EVs derived from fibro‐adipogenic progenitors (FAPs). FAPs influence muscle regeneration by extracellular vesicle‐mediated transfer of microRNA to MuSCs and other cells. HDACi‐induced EV‐miR‐206 enables FAPs to support MuSC‐mediated regeneration of dystrophic muscles. HDACi‐modulated FAP‐EVs induce pro‐regenerative, anti‐fibrotic and immune‐modulatory effects in DMD muscles. Abstract : Pharmacological modulation of microRNA content in extracellular vesicles released by FAPs of Duchenne Muscular Dystrophy (DMD) muscles exposed to epigenetic drugs (HDAC inhibitors) has therapeutic effects via combinatorial targeting of events implicated in DMD pathogenesis.